Peripheral inflammation and neurocognitive functioning in early psychosis: Specific associations of TNF-α and IL-6 with social cognition - Ana Catalán; Claudia Aymerich; José Manuel Rodríguez-Sánchez; Borja Pedruzo; Gonzalo Salazar de Pablo; Patxi Gil; Francisco Aguayo; Garazi Acasuso; Alvaro Collado-Pérez; Javier Goena; Olatz Ibarretxe; Iñaki Zorrilla; et al. (European Psychiatry, 2025)
Abstract Background Cognitive deficits and immune system dysregulation are core features of psychotic disorders. Among inflammatory markers, interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) have been linked to both psychosis pathophysiology and related cognitive impairments.